Phase-based Regional Oxygen Metabolism (PROM) using MRI - Fan, Audrey P. (2011)
Venous oxygen saturation (Y(v)) in cerebral veins and the cerebral metabolic rate of oxygen (CMRO(2)) are important indicators for brain function and disease. Although MRI has been used for global measurements of these parameters, currently there is no established technique to quantify regional Y(v) and CMRO(2) using noninvasive imaging. This paper proposes a technique to quantify CMRO(2) from independent MRI estimates of Y(v) and cerebral blood flow (CBF). The approach uses standard gradient-echo (GRE) and arterial spin labeling (ASL) acquisitions to make these measurements. Using MR susceptometry on gradient-echo phase images, Y(v) was quantified for candidate vein segments in gray matter that approximate a long cylinder parallel to the main magnetic field. Local CBF for the identified vessel was determined from a corresponding region in the ASL perfusion map. Fick’s principle of arteriovenous difference was then used to quantify CMRO(2) locally around each vessel. Application of this method in young, healthy subjects provided gray matter averages of 59.6 ± 2.3% for Y(v), 51.7 ± 6.4 ml/100g/min for CBF, and 158 ± 18 μmol/100g/min for CMRO(2) (mean ± SD, n=12), which is consistent with values previously reported by PET and MRI.